THE ROLE OF INTERNAL CONTROL UNITS IN MITIGATING FINANCIAL MISMANAGEMENT IN GOVERNMENT DEPARTMENTS - Awonke Geqeza (Universitas Nusa Cendana, 2025)
The study explores how internal control units (ICUs) identify, assess, and manage risks related to public fund mismanagement. This study is grounded by control theory, which explains the function of internal control mechanisms to avert financial mismanagement. The study employed the purposive sampling method in sampling respondents. Using a quantitative cross-sectional survey of 150 respondents via interviewer-administered questionnaires, the study identifies relational and predictive factors preventing the curbing of financial mismanagement, such as the reoccurrence of risk associated with unauthorized, irregular, fruitless, and wasteful expenditure. Owing to the management failure to implement ICU recommendations. This research emphasizes the critical role of ICU in mitigating financial mismanagement in government departments, thereby improving public service delivery. The findings of this study call for evidence-based policy changes that prioritize implementation of ICU recommendations by management, independence of compliance units, and strategic leadership units. These changes are essential for mitigating financial mismanagement, enhancing service delivery, and strengthening public trust in government institutions. Keywords: Public Fund Mismanagement; Control Theory; Risk Management in Public; Finance, Mitigation; Government Department